Initial Homosexual Experiences of MSM in Surat City - Mukesh Kumar; RK Bansal (National Journal of Community Medicine, 2010)
This cross-sectional study among 200 Men having sex with men in Surat City explores their initial MSM experiences. Our findings reveal that MSM are sexually active with slightly more bisexual than homosexual. Over half had their first homosexual attraction and relationships before the age of 14 years commonly while playing with friends, though some were forced or raped into their first MSM experience by cousin, friend or elders and care takers. 94% the second homosexual encounter had occurred within 3 months of the first homosexual encounter. These two initial MSM experiences play an important role in future MSM inclinations and highlight the need to ensure that children do not enter into such early relationships before the age of consent. What merits special attention is that these experiences invariably occur during adolescence and their impression makes a lasting effect on their psyche and sexual inclination lifelong.  Receptive anal sex emerges as the most common sexual act (89.5%) and as the commonest reason for continuing with MSM relationships (26.5%). Friends are the main source (99.5%) of entry into an MSM group.